2019
DOI: 10.5603/gp.2019.0029
|View full text |Cite
|
Sign up to set email alerts
|

The clinical usefulness of biochemical (free β-hCg, PaPP-a) and ultrasound (nuchal translucency) parameters in prenatal screening of trisomy 21 in the first trimester of pregnancy

Abstract: Objectives: The aim of the study was to analyze the correlation of multiples of the normal median of PAPP-A, free β-hCG levels and nuchal translucency values in prenatal, first trimester screening of trisomy 21 in pregnant women. Material and methods: 251 pregnant women underwent antenatal screening at 11-13 +6 weeks of pregnancy which was composed of the measurement of free β-human chorionic gonadotropin (β-hCG) and pregnancy-associated plasma protein (PAPP-A) levels in the maternal serum and an ultrasound as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 8 publications
2
13
1
3
Order By: Relevance
“…We defined "low PAPP-A" as PAPP-A <0.5 MoM, based on findings derived from previous studies. 12 Calculations revealed leiomyoma size of 5.5 cm diameter as a cut-off value with 90% (86.7-92.7) specificity and 40% (22.7-59.4) sensitivity for low PAPP-A (Figure 2). Results of ROC curve analysis demonstrated that area under the curve value for leiomyoma size is 0.675 (0.63-0.72) (p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…We defined "low PAPP-A" as PAPP-A <0.5 MoM, based on findings derived from previous studies. 12 Calculations revealed leiomyoma size of 5.5 cm diameter as a cut-off value with 90% (86.7-92.7) specificity and 40% (22.7-59.4) sensitivity for low PAPP-A (Figure 2). Results of ROC curve analysis demonstrated that area under the curve value for leiomyoma size is 0.675 (0.63-0.72) (p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…They established that although the mean NT was significantly higher in fetuses with confirmed trisomy 21 than in euploid fetuses, a considerable proportion of the former group showed normal NT values. For cases with PAPP-A concentrations of less than 0.5 and β-hCG levels of over 1.5 MoM, the figure was 44.15% and 26.5%, respectively [9].…”
Section: Discussionmentioning
confidence: 95%
“…Our results were not statistically significant; however, this issue also occurred in other studies [ 17 , 25 , 28 , 29 , 30 ]. Some authors observed that, in a population of white American, Chinese and Italian women, the combination of the CT and TT genotypes of the c.665C>T MTHFR variant and the GG genotype for the c.66A>G variant in the MTRR (OR = 6.0, p < 0.025; Wang) significantly increased the risk for trisomy 21 in fetuses of women carriers of these alternative genotypes [ 2 , 4 , 21 ]. The lack of statistical significance in our research may depend on the size of the groups and the studied population, because in the Polish population, there are no significant differences in the frequency of the alleles and genotypes of the studied alternative variants between women with fetal trisomy 21 and without the abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasound examination was performed using the Voluson E8 ultrasound (General Electric Company (GE), Fairfield, CT, USA) and included the assessment of fetal anatomy with fetal heart rate (FHR) and measurement of nuchal translucency (NT) as a marker of the risk of chromosomal abnormalities (trisomy 21, 18 and 13), according to the standards of the Fetal Medicine Foundation and recommendations of the Ultrasound Section of the Polish Society of Gynecologists and Obstetricians [ 1 , 2 , 3 , 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation